First facts on the distribution of personal protective equipment during the coronavirus pandemic and facts revealed by medical entities in Brazil: a cross-sectional study - Maluf, Mario Afonso; Nunes, Rui (São Paulo Medical Journal, 2023)
BACKGROUND: The 2019 coronavirus pandemic (COVID-19) has revealed precarious public health conditions worldwide, where serious failures have occurred, similar to the distribution of personal protective equipment (PPE) to physicians in the government of Brazil. OBJECTIVE: The objective of this investigation was to prove through facts that there have been failures in the distribution of PPE to medical professionals within a reasonable timeframe. DESIGN AND SETTING: Through a cross-sectional study, we sought to identify the information and data on the subject of “Distribution of PPE” from the official sites of all the national and regional medical representative entities. METHODS: All medical representative entities, such as unions, councils, and federations, were identified by searching their existing websites, which were active on the World Wide Web, identifying facts, news, and official data regarding the supply of PPE on a daily basis and during the research period. RESULTS: It was evident from the identification of over 3,900 physician complaints and news reports that there was a failure to distribute PPE to medical professionals in Brazil over a reasonable period. Several physicians obtained PPE through the ruling of the courts. CONCLUSIONS: There was indeed a failure in the context of health service administration, which compromised the second level of the Maslow Scale, safety needs, and exposed these professionals to a greater risk than necessary, compromised the quality of work life, and directly compromised the doctor-patient relationship. The condition of the physicians cannot be forgotten during the COVID-19 pandemic.